A PSYCHOLOGICAL PERSPECTIVE ON CULTURAL DIFFERENCE: EPISTEMOLOGICAL HETEROGENEITY AND INDIVIDUAL HETEROGENEITY ACROSS CULTURES - Fatehi, Kamal; Tate, Uday S. (European Scientific Journal, ESJ, 2014)
Most cross-cultural studies of management have been sociological type. Conventional view of cultures and sociological perspective has resulted in the assumption that within each culture members are homogeneous in their psychological make-up, logic, and perspective. Although researchers have reminded us that people vary on pivotal psychological dimensions, both on a between-country and within-country basis, these reminders were not heeded. Maruyama’s theories and research on epistemological heterogeneity, and individual heterogeneity across cultures, or as it is called, mindscape, were the exception. This paper elaborates on epistemological heterogeneity and individual heterogeneity across cultures. It suggests that researchers in international management could use this line of inquiry to expand upon our understanding of effective managerial practices dealing with cultural differences among people.